Treat the unequal as unequal! Inclusion means thinking differently - El-Mafaalani, Aladin [Verfasser] (My University, 2013)
"The concept of inclusion has become established in various fields such as special needs and mainstream school education, social work, migration research and the sociology of education. Even in business administration and management theory, the inclusion of diversity is attracting ever increasing interest, not least from an economic viewpoint. The question this raises, however, is whether this interest is not just 'old wine in new skins'? Why did integration dominate the discourse until quite recently, and why the growing emphasis on inclusion today? This article compares the concepts of inclusion and integration and looks at the different logic of educational practice entailed by each concept. Attention is also directed to the structures and mechanisms of an exclusive German educa tion system. The implementation of an inclusive pedagogy calls for changes to these precise aspects, which will be outlined in the conclusion." (Autorenreferat, BIBB-Doku)
Keywords: P 1.7 Benachteiligte; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Inklusion; Integration; Ausgrenzung; Bildungssystem